2010
DOI: 10.1186/1475-2840-9-61
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure variability in type 1 diabetes subjects and their nondiabetic siblings - influence of erythrocyte electron transfer

Abstract: BackgroundNormotensive non-diabetic relatives of type 1 diabetes (T1D) patients have an abnormal blood pressure response to exercise testing that is associated with indices of metabolic syndrome and increased oxidative stress. The primary aim of this study was to investigate the circadian variability of blood pressure and the ambulatory arterial stiffness index (AASI) in healthy siblings of T1D patients vs healthy control subjects who had no first-degree relative with T1D. Secondary aims of the study were to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…DNA binding activities of clock-like gene products NAPS2:Bmal1 and CLOCK:Bmal1 are sensitive to the redox state of the cell [66]; equally sirtuin 1 (SIRT1) activity that regulates the amplitude and the duration of circadian gene expression depends on NAD ratio [67]. In a clinical setting, we themselves observed in type 1 diabetes families a relationship between daytime SBP and erythrocyte transplasma membrane electron transport activity that is in turn highly correlated with the intracellular balance of the NADH/NAD redox pair [50]. Delezie and Challet have recently reviewed the literature showing that metabolic dysfunction is associated with circadian disturbances at both central and peripheral levels; they highlighted the role of nutrient sensors NAD(H), NADP(H), SIRT1, and AMPactivated protein kinase in ensuring the fine tuning of metabolic and clock regulations [68].…”
Section: The Mechanisms That Have Been Supposed To Underlie the Obsermentioning
confidence: 84%
See 3 more Smart Citations
“…DNA binding activities of clock-like gene products NAPS2:Bmal1 and CLOCK:Bmal1 are sensitive to the redox state of the cell [66]; equally sirtuin 1 (SIRT1) activity that regulates the amplitude and the duration of circadian gene expression depends on NAD ratio [67]. In a clinical setting, we themselves observed in type 1 diabetes families a relationship between daytime SBP and erythrocyte transplasma membrane electron transport activity that is in turn highly correlated with the intracellular balance of the NADH/NAD redox pair [50]. Delezie and Challet have recently reviewed the literature showing that metabolic dysfunction is associated with circadian disturbances at both central and peripheral levels; they highlighted the role of nutrient sensors NAD(H), NADP(H), SIRT1, and AMPactivated protein kinase in ensuring the fine tuning of metabolic and clock regulations [68].…”
Section: The Mechanisms That Have Been Supposed To Underlie the Obsermentioning
confidence: 84%
“…Chronobiologically interpreted 7-day ABPM uncovered MESOR-hypertension and circadian hyper-amplitude-tension in subjects with prediabetes [49]. Twenty-four hour ABPM in type 1 diabetes families evidenced: a) SBP MESOR and pulse pressure were higher in patients with type 1 diabetes; b) DBP acrophase was 3 hours earlier in the diabetic than in normal subjects and DBP ecphasia was more pronounced in patients with lower HR variability during deep breathing; c) non-diabetic siblings of patients with type 1 diabetes showed signs of reduced insulin sensitivity, larger circadian amplitude of SBP and higher ambulatory arterial stiffness index [50]. An analogous relationship was previously observed between SBP ecphasia and reduced HR variability in subjects with type 2 diabetes [51].…”
Section: Evidence For Altered Characteristics Of Blood Pressure Rhythmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent investigation on the circadian variability of blood pressure in T1D families, we have extensively discussed the metabolic derangement that has been documented in non-diabetic siblings of T1D patients. The combination of higher mean FPG, lower HOMA-IS, and lower HbA1c levels suggested that siblings with isolated IFG (thus impaired basal glucose clearance rate) may also have lower postprandial glycemia values (due to enhanced insulin-stimulated muscle glucose disposal) [19].…”
Section: Discussionmentioning
confidence: 99%